The Position and Urgency of the Justice Collaborator in the Crime of Shooting by Richard Eliezer (Ruling Number: 798/Pid.B/ 2022/ PN. Jkt. Sel) - Wahyuni, Sry; Fauzi, Engrina; Salsabila, Kirana (LPPM Universitas Ekasakti, 2023)
The position of witnesses is very important in the trial process because witnesses provide proof of the guilt of the suspect and defendant based on what they saw and experienced. A justice collaborator is a person who is a witness to a criminal act and collaborates with the main perpetrator. If one of the perpetrators of a particular criminal act admits what was done but is not the main perpetrator of the action, they provide information as a witness in the criminal trial. The problems that will be discussed in this research are what is the position of Justice Collaborator in Indonesian criminal law, what is the urgency of Richard Eliezer as Justice Collaborator in the criminal case of the shooting of Joshua Hutabarat (analysis of decision Number: 789/Pid.B/ 2022/PN. Jkt.Sel ). In carrying out this research the author used a method that can answer the problem formulation in this research, namely qualitative with a normative juridical approach. In several cases, the judge handling the Justice Collaborator referred to the Supreme Court Circular No. 04 of 2011 concerning handling Justice Collaborators in certain criminal cases, or SEMA No. 04 of 2011. Protection Regulations carry out protective actions and cooperate with justice. Whistleblowers cannot be prosecuted criminally or civilly for reports or statements made, made, or have been made. However, witnesses cannot be acquitted of criminal charges in the same case if their guilt is clearly proven in court. Because of his testimony, the judge was able to reduce the sentence. The Justice Collaborator is currently regulated by law. The Justice Collaborator is essential to organizing an orderly system of justice and providing effective enforcement and protection for those who are or will be witnesses. It also plays an important role in preventing criminal activity by achieving goals, fostering trust, fostering respect, and encouraging legal cooperation. Supreme Court Circular No. 4 (SEMA) of 2011 states that the government must be involved in investigating cases of witnesses and victims, emphasizing that the idea of justice collaborators is based on the belief that people who are punished for their actions can be used to ensure justice in criminal cases.